Advances in the Statistical Characterization of Fading: From 2005 to Present - José F. Paris (International Journal of Antennas and Propagation)
This review paper presents some of the most significant advances in statistical characterization of wireless communication fading. We will focus on the fundamental statistical characterizations of the fading distributions in terms of the probability density function (PDF), the cumulative density function (CDF), and the moment generating function (MGF). The period from 2005 to present will be considered in order to complement the information which can be found in the specialized literature like Simon and Alouini’s book on digital communications over fading channels. We present both the advances on classical fading models and a brief summary of some selected new fading models. Some open problems in the field will be also stated.